The Kelvin-Helmholtz Instability From the Perspective of Hybrid Simulations - Delamere , P. A.; Barnes , N. P.; Ma , X.; Johnson , J. R. (Frontiers in Astronomy and Space Sciences, 2021)
The flow shear-driven Kelvin-Helmholtz (KH) instability is ubiquitous in planetary magnetospheres. At Earth these surface waves are important along the dawn and dusk flanks of the magnetopause boundary while at Jupiter and Saturn the entire dayside magnetopause boundary can exhibit KH activity due to corotational flows in the magnetosphere. Kelvin-Helmholtz waves can be a major ingredient in the so-called viscous-like interaction with the solar wind. In this paper, we review the KH instability from the perspective of hybrid (kinetic ions, fluid electrons) simulations. Many of the simulations are based on parameters typically found at Saturn's magnetopause boundary, but the results can be generally applied to any KH-unstable situation. The focus of the discussion is on the ion kinetic scale and implications for mass, momentum, and energy transport at the magnetopause boundary.